Pollen Alters Amino Acid Levels in the Honey Bee Brain and This Relationship Changes With Age and Parasitic Stress - Gage, Stephanie L.; Calle, Samantha; Jacobson, Natalia; Carroll, Mark; DeGrandi-Hoffman, Gloria (Frontiers in Neuroscience, 2020)
Pollen nutrition is necessary for proper growth and development of adult honey bees. Yet, it is unclear how pollen affects the honey bee brain and behavior. We investigated whether pollen affects amino acids in the brains of caged, nurse-aged bees, and what the behavioral consequences might be. We also tested whether parasitic stress altered this relationship by analyzing bees infected with prevalent stressor, Nosema ceranae. We measured levels of 18 amino acids in individual honey bee brains using Gas Chromatography – Mass Spectrometry at two different ages (Day 7 and Day 11). We then employed the proboscis extension reflex (PER) to test odor learning and memory. We found that the honey bee brain was highly responsive to pollen. Many amino acids in the brain were elevated, and were present at higher concentration with age. The majority of these amino acids were non-essential. Without pollen, levels of amino acids remained consistent, or declined. Nosema-infected bees showed a different profile. Infection altered amino acid levels in a pollen-dependent manner. The majority of amino acids were lower when pollen was given, but higher when deprived. Odor learning and memory was not affected by feeding pollen to uninfected bees; but pollen did improve performance in Nosema-infected bees. Our results suggest that pollen in early adulthood continues to shape amino acid levels in the brain with age, which may affect neural circuitry and behavior over time. Parasitic stress by N. ceranae modifies this relationship revealing an interaction between infection, pollen nutrition, and behavior.